(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Hypertension or high blood pressure is one of the most common diseases of the vascular system of the heart. this is a disease in which a stable increase in blood pressure is its main manifestation. Risk factors that increase the likelihood of its development have been identified by observing large groups of people. It is often referred to as a" silent killer " (silent killer) because in most cases it develops without any specific symptoms. If not controlled, it leads to serious complications such as heart attack, stroke, kidney failure. Blood pressure is caused by the movement of blood through the vessels. During the contraction of the heart, an increase in pressure (systolic indicator) occurs, and during the relaxation of the organ, a decrease in blood pressure (diastolic indicator) occurs. Hypertension is one of the most common diseases of the cardiovascular system. It can be an independent pathology or the result of diseases of the kidneys, adrenal glands and other organs. This article is about